Bioactivity Profiling of Daedaleopsis confragosa (Bolton) J. Schröt. 1888: Implications for Its Possible Application in Enhancing Women's Reproductive Health - Djordje Ilić; Maja Karaman; Mirjana Bogavac; Jovana Mišković; Milena Rašeta (MDPI AG, 2024)
This study investigates the bioactivity profile of wood-rotting fungal species Daedaleopsis confragosa (Bolton) J. Schröt. 1888, focusing on its antioxidant, cytotoxic, and genotoxic activities and enzyme modulation properties with respect to its possible application in terms of enhancing women's reproductive health. Two types of extracts, including those based on EtOH extraction (DC) and hydrodistillation (DCHD), were investigated. The results indicate that the radical scavenging capacity against the DPPH radical and reduction potential were stronger in the DC extracts owing to the higher total phenolic content (TPC) and total flavonoid content (TFC) (25.30 ± 1.05 mg GAE/g d.w. and 2.84 ± 0.85 mg QE/g d.w., respectively). The same trend was observed in the protein phosphatase-1 (PP1) activity and in the genotoxic activity against the δ virus since only the DC extract exhibited DNA disintegration regarding a dilution of 1:100. Conversely, the DCHD extract exhibited increased hemolytic and cytotoxic effects (339.39% and IC50 = 27.76 ± 0.89 μg/mL-72 h incubation, respectively), along with greater inhibition of the AChE enzyme (IC50 = 3.11 ± 0.45 mg/mL) and hemolytic activity. These results suggest that terpenoids and steroids may be responsible for the observed activity in DCHD as these compounds could potentially be extracted following the HD procedure. This comprehensive bioactivity profiling offers valuable insights into the potential therapeutic applications of D. confragosa from Serbia and underscores the importance of further investigations for harnessing its pharmacological potential.